1996
DOI: 10.1016/0014-5793(96)00190-1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the cytosolic chelatable iron pool of K562 cells

Abstract: The labile iron pool of cells (LIP) constitutes the primary source of metabolic and catalytically reactive iron in the eytosol. We studied LIP homeostasis in K562 cells using the fluorescent metal-sensitive probe calcein. Following brief exposure to iron(ll) salts or to oxidative or reductive stress, LIP rose by up to 120% relative to the normal level of 350 nM. However, the rate of recovery to normal LIP level differed markedly with each treatment (respective tl/2s of 27, 65-88 and -<17 min). We show that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(56 citation statements)
references
References 29 publications
2
53
1
Order By: Relevance
“…It has been shown that cells treated with lower than 25 M iron (supplied as FAC) are able to maintain an equilibrium between LIP and iron bound to ferritin without a disturbance in cellular metabolism (45). Results of the present in vitro study demonstrate, for the first time, that treatment of normal human skin fibroblasts with such concentrations of iron can up-regulate tropoelastin synthesis and its final extracellular deposition into elastin fibers.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…It has been shown that cells treated with lower than 25 M iron (supplied as FAC) are able to maintain an equilibrium between LIP and iron bound to ferritin without a disturbance in cellular metabolism (45). Results of the present in vitro study demonstrate, for the first time, that treatment of normal human skin fibroblasts with such concentrations of iron can up-regulate tropoelastin synthesis and its final extracellular deposition into elastin fibers.…”
Section: Discussionmentioning
confidence: 55%
“…Confluent cultures were then treated for 72 h with or without FAC producing iron concentrations from 2 to 200 M. The low iron concentration (2 and 20 M) of iron utilized in the present study remained in the range that did not induce any disturbances in cellular metabolism when tested by other investigators (45). The high iron concentration (200 M) was comparable to concentrations used in studies of iron overload (41,46).…”
Section: Methodsmentioning
confidence: 61%
See 1 more Smart Citation
“…The excess iron deposition is associated with fibrosis and cirrhosis [33]. Oxidative damage in K562 cells is associated with the appearance LIP after treatment with transferrin-bound iron or FAC [34]. Both ferric and ferrous ions have been reported to induce lipid peroxidation in HepG2 cells [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…The labile iron pool of cells constitutes a cytosolic fraction of low molecular weight (LMW) chelators bound iron or bioavailable iron, which can be characterized as iron (a) exchangeable and chelatable; (b) easily bioavailable for uptake by ferritin, heme, transferrin, or chelators; (c) metabolically and catalytically reactive for oxidant formation and likely responsible for iron toxicity; (d) possibly having regulatory properties which may affect iron responsive element-binding protein activity per se. 31,32 Recently iron status has been examined as a contributor to carcinogenesis, [33][34][35][36][37][38] and has been associated with increased risk of cancer in several epidemiological studies. 34,37,38 Factors which increase reactive oxygen species, such as smoking, inflammation, bioavailable iron, and reduced antioxidant activity may adversely affect the natural history of HPV infections by increasing the oxidant:antioxidant balance and directly influence transcriptional activity.…”
Section: Hpv and Cervical Carcinogenesismentioning
confidence: 99%